ChemInform Abstract: Synthesis and Reactivity of N‐tert‐Butanesulfinyl Glycosylamines. Issue 47 (November 2015) - Cocaud, Chloe; Nicolas, Cyril; Bayle, Alexandre; Poisson, Thomas; Pannecoucke, Xavier; Martin, Olivier R.
Abstract: The reaction of furanose and pyranose derivatives with optically active sulfinamidine (II) gives the title compounds (III) and (VII), respectively.